Penerapan Ekstrakurikuler Rohis dalam Membentuk Karakter Religius pada Peserta Didik di SMP Negeri 9 Kota Serang - Fadli Rahdiat Gunadi; Anisa Tulhalizah; Nur Hidayatil Janah; Delsa Miranty (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
The research carried out has the aim of knowing the way or application of the school in shaping religious-based character, at the junior high school level in extracurricular rohis, using descriptive qualitative research methods whose research subjects are several students who are part of extracurricular rohis members. The school becomes a place that is intended to be able to obtain formulations about ways or efforts in shaping the religious character of students through extracurricular rohis, while in carrying out the research applying data collection techniques in the form of, observation and interviews. The results of the interviews that have been carried out show that students who take part in Rohis extracurricular activities at Junior High School gain a lot of knowledge about Islam, to skills in playing marawis musical instruments, so that students' insights and skills can increase.